APOLOGY STRATEGIES USED BY KEVIN RUDD IN HIS STOLEN GENERATION SPEECH - RORONJAWI, WILIS (Jurnal Ilmiah Mahasiswa FIB, 2014)
Roronjawi, Wilis. 2014. Apology Strategies Used by Kevin Rudd in His StolenGeneration Speech. Study Program of English, Universitas Brawijaya. Supervisor:Iis Nur Rodliyah, Co-supervisor: Yana Shanti Manipuspika.Key Words: Speech Acts, Apology, Apology Strategies, Stolen Generation Speech.When people make fault or offense that may hurt other people incommunication, they have to do something to repair it in order to make therelationship better. Apology can be the first step that can repair a good relationship. Apology strategies are important to learn in order to know how people ask for an apology appropriately. This study discusses apology strategies by Kevin Rudd in his Stolen Generation speech. The study was conducted in order to find out the types of apology strategies used in Kevin Rudd’s Stolen Generation speech and how the utterances of the speech help repairing the relationship between Australian government and Indigenous people of Australia  This study applied qualitative approach in which the data were collected in theform of words or sentences. The data were the utterances containing apologystrategies in Kevin Rudd Stolen Generation speech and the data source was the Stolen Generation speech by Kevin Rudd. The researcher read the script then the selected utterances which contain apology was marked to be more easily analyzed. Thus, the researcher identified the types of apology by putting into a table then drawing conclusion of all findings that had been analyzed.This study revealed that there are six categories and eight sub-categories ofapology strategies in Kevin Rudd’s Stolen Generation speech that were found. Those were acknowledge of responsibility which is reflected in implicit acknowledgement and explicit acknowledgement sub-categories, explanation or account which is reflected in explicit explanation sub-category, expression of apology which is reflected in expression of regret, offer of apology and request for forgiveness subcategories, offer of repair which is reflected in repair and compensation subcategories, promise of forbearance and expressing concern for hearer categories. The expression of concern for hearer and promise for forbearance were mostly used in conducting the speech because the speech wanted to give respect, showed the promise not to do the mistreatment and wanted the Indigenous people forgive the government of Australia.For the next researchers, it is recommended that they use other theories ofapology strategies from other experts in digging up apology strategies. The next researchers are also suggested to use another object in order to broaden the comprehension in apology strategies.